If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(d + -4) = 15 Reorder the terms: 3(-4 + d) = 15 (-4 * 3 + d * 3) = 15 (-12 + 3d) = 15 Solving -12 + 3d = 15 Solving for variable 'd'. Move all terms containing d to the left, all other terms to the right. Add '12' to each side of the equation. -12 + 12 + 3d = 15 + 12 Combine like terms: -12 + 12 = 0 0 + 3d = 15 + 12 3d = 15 + 12 Combine like terms: 15 + 12 = 27 3d = 27 Divide each side by '3'. d = 9 Simplifying d = 9
| 8=4c-4 | | 4x+7,x=6 | | 6r+6=21r+9 | | y=2140x-53500 | | 47=11+12W | | 3/4+10=190 | | 8y+5x-3y+7-2x= | | 2x-5=4x-1+5 | | log[9]x=log[9]5+log[9]6-log[9]3 | | -5(1+2w)=20 | | 4x-16+6=2x+-6+2x | | 2-4x=-62 | | 1/2x-5+2x+2=10 | | -5(-1+k)=25 | | 7x+21=x/7 | | (d+1)=64 | | 3y+6y+8y= | | 2/3*2*-8= | | -4x+9x=-50 | | x^3+15x^2+72x+108=0 | | 4y-10=6+y | | 2x^2+25x+48=0 | | 3/8*2/3 | | 4/3+2=14/3 | | 2/5(f+6)-f | | 7y-63/2=-4y | | 7x^2+9y^2=-2 | | a=400-116-.38 | | 3/4+2=14/3 | | X^3-8-x^2-4=0 | | k-12=3 | | 0=12x^2+5x-29 |